Abusi sessuali nella Chiesa e ambivalenza dell'eros: una provocazione per la fede - Imperatori, Mario (Rassegna di teologia, 2018)
In the present liquid context, the centuries-old disregard of the fecund sexual distinction forces to choose between the nuptial interpretation of Revelation and the sinking in the whirl of an eros left to itself; an eros that just the abuses satanically testify to be present at the very heart of the church. And that so requires a supplement of faith in its nuptial Mystery, as to pity (suffer-with) the Passio that the Body of Christ is suffering for the salvation of the world.